consumer attitude towards exide BATTERIES - kumar, Dr. L.Sathees (International Journal of Psychosocial Rehabilitation, 2020)
This study is conducted on Consumer attitude towards Exide Batteries in Salem City. The data are to be collected from both primary and secondary sources. The objectives of the study is to find out the performance of the company and the level of satisfaction obtained from the customers. To study the dealers perception towards the products. To find out the customer preference towards the products. To find out new features for the development of Exide battery. To study the problem faced by the customers and dealers and the company’s support provided towards the same and suggest measures to solve the problem. The sample size selected for this research is 100 respondents which include users of Exide Batteries. The technique used for the research is a random sampling technique because the population is finite. The various tools and techniques adopted in this study are Percentage Analysis, Weighted Average Method (for ranking questions) and Chi-square Test. It was suggested from the findings that the public point of view is that more advertisements required to make aware about Exide Batteries equivalent to other batteries like Amaron, Exide and reset batteries. Dealers suggested that the company possesses ISO 9001 - 2000 certification and the also have an advantage that Exide’s spare parts are easily available in the market with reasonable price.